Hazards of hospital cleaners in a tertiary health facility in Southwest Nigeria - Olayinka Stephen Ilesanmi; Bridget Omotoso; Darlington Falana (Occupational Health and Safety Society of Nepal, 2015)
Introduction: Hospital cleaning job is outsourced to companies that employ unskilled cleaners. Despite being an important role, little attention is paid to the work place hazards hospital cleaners are exposed. Objective: This study therefore aimed at determining the prevalence of and factors associated with occurrence of work related hazards among hospital cleaners at Federal Medical Centre, Owo, Ondo State, Nigeria. Methods: A cross-sectional study of 249 hospital cleaning staff was conducted. A semi-structured interviewer administered questionnaires were used to obtain information on sociodemographic characteristics and work place related hazards. Descriptive statistics were done and associations were explored with the chi square test at 5% level of significance. Result: The mean age of respondent was 34 ± 7 years, (range 20 - 60 years), 142(57.0%) attended secondary school. In all, 67.7% of the cleaners spent < 8 hours at work daily. Chemical hazards affected 79.1% females compared to 57.9% of the males (p=0.03). Also, 60% of those with primary education had mechanical hazards compared to 39.1% of those with tertiary education. (p=0.02). Mechanical hazards occur in 53.8% cleaners sitting for < 5hours compared to 38.1% sitting ≥ 5hours at work daily (p=0.03). Respondents were exposed to physical, chemical, mechanical, and biological hazards. Conclusion: Various forms of hazards were reported by the cleaners studied. Research can be undertaken to reduce hospital cleaners exposure to hazards